(untitled) (Research, Society and Development, 2021)
The existence and preservation of urban parks or areas with vegetation remnants in may densely urbanized environments is an important alternative to maintain the hydrological functions of the soil next to its natural characteristics, mitigating the imbalances arising from urban densification in physical processes, especially hydrological. In this sense, the present study aimed to evaluate the hydrological efficiency of areas with remaining vegetation in the watershed of the Botafogo stream in Goiânia. The methodology comprised the evaluation of estimates of runoff velocity, effective precipitation, infiltration potential and runoff coefficient of areas that underwent urban densification and areas that remained preserved between the years 1988, 1998, 2008 and 2018. The results indicate an average increase of 3.8 m/s in runoff velocities, increased effective precipitation, reduced infiltration potential, as well as increased runoff coefficients, especially in densely urbanized areas. For the preserved areas the tendency was to maintain the values of hydrological variables in the evaluated period. It is noteworthy that the remaining vegetation areas tend to suffer the effects of surface runoff from densely urbanized areas located upstream, with the concentrated runoff causing erosive processes even in vegetated areas. Thus, the importance of maintenance as well as the installation of green areas in urban environments is highlighted as a way to mitigate imbalances, especially those related to hydrological functions of the soil.